2023
DOI: 10.1002/dmrr.3646
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on the diagnosis and treatment of active Charcot neuro‐osteoarthropathy in persons with diabetes mellitus (IWGDF 2023)

Abstract: The International Working Group on the Diabetic Foot (IWGDF) has published evidence‐based guidelines on the prevention and management of diabetic foot disease since 1999. This is the first guideline on the diagnosis and treatment of active Charcot neuro‐osteoarthropathy in persons with diabetes published by the IWGDF. We followed the GRADE Methodology to devise clinical questions in the PACO (Population, Assessment, Comparison, Outcome) and PICO (Population, Intervention, Comparison, Outcome) format, conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 153 publications
0
29
0
1
Order By: Relevance
“…In a prospective study of 1666 people with diabetes, equinus deformity was present in 10.3% . Charcot arthropathy, defined as a foot fracture with possible joint dislocation in people with peripheral neuropathy, affects approximately 0.3% of people with diabetes, can lead to significant deformity, and increases the risk of a diabetic foot ulcer, particularly in the midfoot and ankle/hindfoot . Although approximately 40% of people with Charcot arthropathy have concomitant tissue loss, a unilateral red, hot, swollen foot without a wound or diagnosis of deep vein thrombosis may indicate Charcot arthropathy …”
Section: Screening For Risk Of Diabetic Foot Ulcersmentioning
confidence: 99%
“…In a prospective study of 1666 people with diabetes, equinus deformity was present in 10.3% . Charcot arthropathy, defined as a foot fracture with possible joint dislocation in people with peripheral neuropathy, affects approximately 0.3% of people with diabetes, can lead to significant deformity, and increases the risk of a diabetic foot ulcer, particularly in the midfoot and ankle/hindfoot . Although approximately 40% of people with Charcot arthropathy have concomitant tissue loss, a unilateral red, hot, swollen foot without a wound or diagnosis of deep vein thrombosis may indicate Charcot arthropathy …”
Section: Screening For Risk Of Diabetic Foot Ulcersmentioning
confidence: 99%
“…The only controlled study regarding joint arthrodesis in combination with offloading devices compared to offloading devices alone is based on a population of people with Charcot midfoot deformity and DFUs, and that study found little-to-no difference in healing. 43 That paper is included in the guideline on the Charcot foot, 32 and hence, we have considered a recommendation was not justified.…”
Section: Otherwise Please Refer To the Comments In Recommendation 5bmentioning
confidence: 99%
“…Charcot neuro-osteoarthropathy is an inflammatory process in a person with peripheral neuropathy that results in injury to the bones, joints and soft tissues of the lower extremity. 48 CNO, one of the most F I G U R E 5 Halving the global diabetic foot burden from 2% to 1%. DFD, Diabetic foot disease; PAD, peripheral artery disease.…”
Section: Epidemiologymentioning
confidence: 99%
“…devastating complications from diabetes-related neuropathy, can occur in any person with underlying neuropathy. 48 When left untreated, CNO often results in significant foot or ankle deformity that drastically increases the risk of ulceration, infection and amputation. 49 Multiple studies have also demonstrated that these significant physical impacts also result in considerable QoL reductions.…”
Section: Epidemiologymentioning
confidence: 99%